2016
DOI: 10.5194/tc-10-1245-2016
|View full text |Cite
|
Sign up to set email alerts
|

Which are the highest peaks in the US Arctic? Fodar settles the debate

Abstract: Abstract. Though an outstanding achievement for their time, the United States Geological Survey (USGS) topographic maps of the eastern Alaskan Arctic nonetheless contain significant errors, and in this paper we address one of them. Specifically, USGS maps of different scale made in the late 1950s alternate between Mt. Chamberlin and Mt. Isto as the tallest peak in the US Arctic. Given that many of the peaks here are close in height and covered with glaciers, recent climate change may also have changed their he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…These data were acquired using a Nikon DSLR attached to a survey grade Global Navigation Satellite System (GNSS) on board a manned aircraft, providing photocenter position to 10 cm or better and thus eliminating the need for ground control. Accuracy within this steep moun- tain environment was found to exceed 20 cm horizontally and vertically (Nolan and DesLauriers, 2016), without the use of ground control. Data acquisition methods are described in detail in Nolan et al (2015).…”
Section: High-resolution Photogrammetrymentioning
confidence: 87%
See 1 more Smart Citation
“…These data were acquired using a Nikon DSLR attached to a survey grade Global Navigation Satellite System (GNSS) on board a manned aircraft, providing photocenter position to 10 cm or better and thus eliminating the need for ground control. Accuracy within this steep moun- tain environment was found to exceed 20 cm horizontally and vertically (Nolan and DesLauriers, 2016), without the use of ground control. Data acquisition methods are described in detail in Nolan et al (2015).…”
Section: High-resolution Photogrammetrymentioning
confidence: 87%
“…The third tallest peak in the range, Mount Chamberlin (2712 m a.s.l. ; Nolan and DesLauriers, 2016) lies 3 km east of Lake Peters.…”
Section: Site Descriptionmentioning
confidence: 99%
“…The locations of the trail cameras to their tops (the offset was then subtracted to the center of lens for each camera) were surveyed using a Leica GS14 Performance Smart Antenna dGPS because it has been demonstrated that accurate SfM models can be generated from only the known camera positions and orientations, called direct georeferencing (Hugenholtz et al 2016;Nolan and DesLauriers 2016). Targets were also positioned above the headwall of the slumps (visible in the field of view of the cameras because the terrain slopes upward) to provide additional anchoring points.…”
Section: Time-lapse Imagery Using Stationary Trail Camera Arraymentioning
confidence: 99%
“…An alternative is ‘direct georeferencing’, in which control is provided through measurements of camera orientations only (Cramer et al , ; Förstner et al , ). By not requiring ground‐based measurements, the direct approach has a critical advantage for aerial survey over hazardous terrain, and has been shown capable of measurement precisions of order 0·1 m for piloted SfM‐based surveys with survey‐grade GPS synchronised with image capture (Nolan et al , ; Nolan and DesLauriers, ). However, for most current consumer UAVs, precise directly georeferenced work is prevented by their use of low‐quality, multi‐metre precision, on‐board GPS (Carbonneau and Dietrich, ) but survey‐grade GPS is being increasingly installed (Bláha et al , ; Chiang et al , ; Rehak et al , ; Turner et al , ; Eling et al , ; Gabrlik, ; Mian et al , ; Hugenholtz et al , ) and such systems are likely to develop into widespread, invaluable tools for geomorphological research.…”
Section: Introductionmentioning
confidence: 99%